P1-S2.59 Oropharyngeal human papillomavirus (HPV) prevalence and risk factors in men having sex with men (MSM). (10th July 2011) - Read, T; Vodstrcil, L; Tabrizi, S; Garland, S; Grulich, A; Hocking, J; Catriona, B; Chen, M; McCullough, M; Fairley, C
Abstract : Background: HPV-associated oropharyngeal cancers are becoming more common. We sought to determine the prevalence of, and risk factors for oropharyngeal HPV infection in MSM, and to compare the sensitivity of throat swab, oral rinse and absorbed rinse specimens. Methods: Cross-sectional study of 500 MSM (half with HIV infection) attending Melbourne Sexual Health Centre in 2010. Men completed a behavioural questionnaire, provided a self-administered throat swab and a gargled saline sample. Half the saline was absorbed in a tampon, to be suitable for postage. If HPV was present on type-common polymerase chain reaction, it was typed by linear array. ORs for risk factors were calculated by logistic regression. Results: At least one type of HPV was found in 74 of 500 men, a prevalence of 14.8% (95% CI 11.7% to 17.9%) and HPV type 16 was found in 2.8% (95% CI 1.4% to 4.3%). Prevalence of any oropharyngeal HPV was 21.9% in HIV-infected men and and 8% in HIV-negative men—univariate OR 3.2 (95% CI 1.8% to 5.8%). The number of oral sex partners in the previous 2 weeks or previous year was not significant. After multivariate analysis, HIV status was no longer significant. But smoking, older age or higher numbers of reported lifetime oral sex partners all remained significant (Abstract P1-S2.59 table 1 ). Conclusions: Oropharyngeal HPV was more than twice as prevalent in HIV-infected MSM as in HIV-negative MSM, likely due to confounding by older age and higher numbers of lifetime sexual partners in this group.